2016
DOI: 10.3390/ijerph13121248
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Lifestyle Change—Participatory Design of Support Together with Persons with Obesity in the Third Age

Abstract: Sustainable lifestyle changes due to obesity are difficult to achieve regardless methods used. We need to know more about the lived experience of obesity and older persons’ needs for support to make a sustainable change. This paper focuses on the need-finding process in designing support for a sustainable lifestyle change. Multistage focus group interviews were conducted with persons aged 61–72 living in Northern Sweden. A participatory and appreciative reflection and action (PAAR) approach was used in the gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Allin et al 50 also reported that users might need different kinds of information, while some of them may use the Internet to find particular information. Wiklund Axelsson et al 51 also indicated that the study group reported a feeling of being abandoned due to the lack of continuous communication.…”
Section: Discussionmentioning
confidence: 96%
“…Allin et al 50 also reported that users might need different kinds of information, while some of them may use the Internet to find particular information. Wiklund Axelsson et al 51 also indicated that the study group reported a feeling of being abandoned due to the lack of continuous communication.…”
Section: Discussionmentioning
confidence: 96%
“…When there was a conflict in a group, the participants had smaller weight reduction 19 . In a study among older adults, researchers found that group interventions for weight reduction must focus on social activities and health identity instead of a weight identity 20 . Reflection concerning the way of living related to the emotional balance, as one part of the support in a group, contributed to sustainable weight reduction.…”
Section: Introductionmentioning
confidence: 99%
“… 19 In a study among older adults, researchers found that group interventions for weight reduction must focus on social activities and health identity instead of a weight identity. 20 Reflection concerning the way of living related to the emotional balance, as one part of the support in a group, contributed to sustainable weight reduction. The weight change was more considerable if the individual focused on health and well‐being instead of an identity focus determined by weight.…”
Section: Introductionmentioning
confidence: 99%